ANALISIS PROSES REKRUTMEN DAN PROSES SELEKSI TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT Javas Tripta Sejahtera) - Jeffry Kurniawan Winatha (Ma Chung Press, 2018)
Background of the recruitment process and selection process is the first step for a company to be able to obtain qualified and qualified workforce, so as to support the achievement of corporate goals well. Through this selection is expected to provide correct information about the capabilities and skills of prospective workers who through recruitment. We also know that the process of recruitment and selection process conducted by the company, in addition to taking a long time also requires a lot of money. Therefore, many companies do not want to be burdened with issues relating to the recruitment and selection process. If the company can execute this process in an appropriate, honest, thorough, and objective way, then it can be ensured that the company will be able to save company costs and get good and qualified worker candidates. Employee performance is an effort that individuals spend in devoting a certain amount of energy to the job